EFEK KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP MOTIVASI KERJA SERTA IMPLIKASINYA PADA KINERJA PEGAWAI DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KABUPATEN MUSI BANYUASIN - Yulisman, Muhamad (P3M STIE Mulia Darma Pratama, 2025)
ABSTRACT Work performance is the quality and quantity of output achieved by employees when carrying out their duties in line with the responsibilities assigned to them. This study aims to determine how compensation and the work environment affect work motivation and, in turn, their implications for employees of the Department of Public Works and Spatial Planning (PUPR) of Musi Banyuasin Regency. A census (saturated) sampling technique was used, resulting in 68 respondents. The research adopted aquantitative, descriptive approach and employed Structural Equation Modeling (SEM). The key findings are as follows: Compensation (X1) has a positive, significant effect on work motivation (Y), with a T‑statistic of 3.983 > 1.960 and a p‑value of 0.000 < 0.05. The work environment (X2) also positively influences work motivation, indicated by a T‑statistic of 4.444 > 1.960 and a p‑value of 0.000 < 0.05. Compensation (X1) directly affects performance, as shown by a T‑statistic of 2.687 > 1.960 and a p‑value of 0.007 < 0.05. The work environment (X2) exerts a positive, significant effect on performance, with a T‑statistic of 2.610 > 1.960 and a p‑value of 0.009 < 0.05. The coefficient of determination (R²) for the mediating variable, work motivation, is 0.960, meaning 96 % of its variance is explained by the exogenous variables (compensation and work environment). The R² for the latent variable, performance, is 0.962, indicating that 96.2 % of its variance is likewise explained by the same exogenous variables. Keywords: Compensation, Work Environment, Work Motivation, Performance